2020
DOI: 10.3390/rs12030516
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Support Vector Machine and Random Forest Algorithms for Invasive and Expansive Species Classification Using Airborne Hyperspectral Data

Abstract: Invasive and expansive plant species are considered a threat to natural biodiversity because of their high adaptability and low habitat requirements. Species investigated in this research, including Solidago spp., Calamagrostis epigejos, and Rubus spp., are successfully displacing native vegetation and claiming new areas, which in turn severely decreases natural ecosystem richness, as they rapidly encroach on protected areas (e.g., Natura 2000 habitats). Because of the damage caused, the European Union (EU) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(76 citation statements)
references
References 56 publications
5
69
0
2
Order By: Relevance
“…Experiments are conducted on small datasets and overall accuracy in the competitors is less than 80%. A study by [86] suggested the classification of three expansive plant species using SVM and RF for their accurate identification of hyperspectral images. However, in this study, a low F1 score is achieved even when a small number of training sets are used.…”
Section: B Classification Based Approaches Used For Load Balancingmentioning
confidence: 99%
“…Experiments are conducted on small datasets and overall accuracy in the competitors is less than 80%. A study by [86] suggested the classification of three expansive plant species using SVM and RF for their accurate identification of hyperspectral images. However, in this study, a low F1 score is achieved even when a small number of training sets are used.…”
Section: B Classification Based Approaches Used For Load Balancingmentioning
confidence: 99%
“…Recently, non-parametric classifiers are increasingly employed in vegetation classification [4][5][6][7][8] because of their more flexible approach to training data use than in parametric classifiers,…”
Section: Introductionmentioning
confidence: 99%
“…The classification procedure was conducted with the use of e-Cognition Developer as an automated process, along with a classification error matrix [92] and accuracy assessment summary including overall, user, and producer accuracy and Kappa measure [93]. Automation of the classification process allowed us to test several of the most popular classifiers implemented in e-Cognition: random forest (RF) [94], support vector machine (SVM) [95,96], and K-nearest neighbor (KNN) [97]. Each classifier received the same input parameters: brightness, degree of skeleton branching, curvature, and textures after Haralick [98] (GLCM homogeneity, entropy, mean, dissimilarity).…”
Section: Geobia Classification Methodologymentioning
confidence: 99%